Review of ‘Contributions to understanding climate interactions: stratospheric ozone’ by Gennadi Milinevsky, Asen Grytsai, Oleksandr Evtushevsky, and Andrew Klekociuk. (2022) - S. Krakovska (Ukrainian Antarctic Journal, 2023)
Review of ‘Contributions to understanding climate interactions: stratospheric ozone’ by Gennadi Milinevsky, Asen Grytsai, Oleksandr Evtushevsky, and Andrew Klekociuk.  (2022). Kyiv, Akademperiodyka, 252 pp. ISBN: 978-966-360-471-8.Investigations of atmospheric ozone have been fast developing in the last two centuries. Their importance became more evident after the ozone hole discovery in the mid-1980s. Today, it is clear that stratospheric ozone is essential for the Earth’s biosphere, and its content (which conditionally may be named ‘ozone layer thickness’) varies and is determined by different chemical and dynamical processes. In this book, a team of authors considers mainly the physical, particularly dynamic processes influencing ozone in the Earth’s atmosphere. The monograph has seven chapters. It studies the ozone layer, primarily focusing on the middle and high latitudes. Ukrainian researchers wrote the book in co-authorship and long-term cooperation with their Australian colleague, famous atmospheric researcher, Dr. Andrew Klekociuk. The authors are experts in atmospheric physics and present their own results and a review of the current state of the ozone-climate interaction problems. The book includes many references to the recent scientific publications that direct readers to more detailed information to understand the topic better.